Decreased expression of miR-21, miR-26a, miR-29a, and miR-142-3p in CD4⁺ T cells and peripheral blood from tuberculosis patients. - Katja Kleinsteuber (Public Library of Science (PLoS), 2013)
The vast majority of Mycobacterium tuberculosis (M. tuberculosis) infected individuals are protected from developing tuberculosis and T cells are centrally involved in this process. MicroRNAs (miRNA) regulate T-cell functions and are biomarker candidates of disease susceptibility and treatment efficacy in M. tuberculosis infection. We determined the expression profile of 29 selected miRNAs in CD4(+) T cells from tuberculosis patients and contacts with latent M. tuberculosis infection (LTBI). These analyses showed lower expression of miR-21, miR-26a, miR-29a, and miR-142-3p in CD4(+) T cells from tuberculosis patients. Whole blood miRNA candidate analyses verified decreased expression of miR-26a, miR-29a, and miR-142-3p in children with tuberculosis as compared to healthy children with LTBI. Despite marked variances between individual donor samples, trends of increased miRNA candidate expression during treatment and recovery were observed. Functional in vitro analysis identified increased miR-21 and decreased miR-26a expression after re-stimulation of T cells. In vitro polarized Interleukin-17 positive T-cell clones showed activation-dependent miR-29a up-regulation. In order to characterize the role of miR-29a (a described suppressor of Interferon-γ in tuberculosis), we analyzed M. tuberculosis specific Interferon-γ expressing T cells in children with tuberculosis and healthy contacts but detected no correlation between miR-29a and Interferon-γ expression. Suppression of miR-29a in primary human T cells by antagomirs indicated no effect on Interferon-γ expression after in vitro activation. Finally, classification of miRNA targets revealed only a moderate overlap between the candidates. This may reflect differential roles of miR-21, miR-26a, miR-29a, and miR-142-3p in T-cell immunity against M. tuberculosis infection and disease.